Application of Finite Difference Time Domain Technique to Left-Handed Materials - Işık, Işıl Nurdan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
The aim of this thesis is to simulate left handed materials (metamaterials) by using the finite difference time domain (FDTD) method. One dimensional (1D) simulations are carried out using Matlab and for two dimensional (2D), MTM-FDTD Virtual Tool is used. FDTD method is used for 1D and 2D simulations to observe wave behavior in metamaterial slab. 1D simulation of air-dielectric-air media were studied for comparison with 1D air-metamaterial-air simulation. In 1D air-dielectric-air simulation, reflection, transmission and a decreased in wave amplitude were observed as wave propagated through the dielectric slab with positive refractive index whereas in 1D air-metamaterial-air simulation exponentially growing wave has been occurred in the metamaterial slab which have a negative refractive index. Also, no reflection was observed in this simulation, therefore, making the simulation successful in meeting the theory. 2D simulations were studied in air-metamaterial-air media by defining different negative refractive indexes for the metamaterial slabs. Different scenarios were tested, the perfect lens behavior was observed with metamaterial slabs having refractive index -1 and all results were found to be consistent with other studies in the literature. Keywords: Metamaterials, Finite Difference Time Domain (FDTD), Perfect Lens, Negative Refractive Index, Left-Handed Materials

ÖZ: Bu tezin amacı zamanda sonlu farklar (FDTD) yöntemini kullanarak metamalzemelerin simüle edilmesidir. Bir boyutlu (1B) simülasyonlar Matlab kullanılarak, iki boyutlu (2B) simülasyonlar MTM-FDTD sanal aracı kullanılarak yapılmıştır. Zamanda sonlu farklar yöntemi, metamalzeme içerikli levhanın içindeki dalga hareketini gözlemlemek için kullanılmıştır. 1B hava-metamalzeme-hava simülasyonu ile karşılaştırma yapabilmek amacıyla 1B hava-dielektrik-hava simülasyonu çalışılmıştır. 1B hava-dielektrik-hava simülasyonunda elektromanyetik dalga pozitif kırılma indisi olan dielektrik ortamdan geçerken yansıma, iletim ve dalga yüksekliğinde düşüş gözlenmiştir. Oysa 1B hava-metamalzame-hava simülasyonunda negatif kırılma indisi olan metamalzeme içerisinde katlanarak büyüyen dalga oluşmuş ve bu simülasyonda hiç yansıma gözlemlenmemiştir. Bu sonuçlar simülasyonların teori ile uyumlu ve başarılı olduğunu göstermiştir. Metamalzemeler için değişik negatif kırılma indisleri tanımlanarak 2B hava-metamalzeme-hava simülasyonları çalışılmıştır. Değişik senaryolar tasarlanıp, simüle edilmiş, negatif kırılma indisi -1 olan metamalzemelerle mükemmel lens davranışı gözlemlenmiş ve sonuçlar literatürdeki çalışmalarla tutarlı bulunmuştur. Anahtar Kelimeler: Metamalzemeler, Zamanda Sonlu Farklar Yöntemi (FDTD), Mükemmel Lens, Negatif Kırılma İndisi, Sol-Elli Materyaller
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2013. Supervisor: Assist. Prof. Dr. Rasime Uyguroğlu.
Keywords: Electrical and Electronic; Metamaterials - Electronic apparatus and appliances - Materials; Materials - Synthetic products; Metamaterials; Finite Difference Time Domain (FDTD); Perfect Lens; Negative Refractive Index